Ratings of Perceived Exertion and Self-reported Mood State in Response to High Intensity Interval Training. A Crossover Study on the Effect of Chronotype - Vitale, Jacopo A.; La Torre, Antonio; Baldassarre, Roberto; Piacentini, Maria F.; Bonato, Matteo (Frontiers in Psychology, 2017)
The aim of this study was to investigate the influence of chronotype on mood state and ratings of perceived exertion (RPE) before and in response to acute high intensity interval exercise (HIIE) performed at different times of the day. Based on the morningness-eveningness questionnaire, 12 morning-types (M-types; N=12; age 212 years; height 1795 cm; body mass 7412 kg) and 11 evening-types (E-types; N=11; age 212 years; height 18111 cm; body mass 7611 kg) were enrolled in a randomized crossover study. All subjects underwent measurements of Profile of Mood States (POSM), before (PRE), after 12 (POST12) and 24 hours (POST24) the completion of both morning (08.00 am) and evening (08.00 p.m.) training. Additionally, Global Mood Disturbance (GMD), and Energy Index (EI) were calculated. RPE was obtained PRE and 30 min POST HIIE. Two-way ANOVA with Tuckey’s multiple comparisons test of POMS parameters during morning training showed significant differences in fatigue, vigour and EI at PRE and POST24 between M-types and E-types. In addition, significant chronotype differences were found only in POST12 after the evening HIIE for fatigue, vigour and EI. For what concerns Borg perceived exertion, comparing morning versus evening values in PRE condition, an higher RPE was observed in relation to evening training for M-types (P=0.0107) while E-types showed higher values in the morning (P=0.008). Finally, intragroup differences showed that E-types had a higher ratings of perceived exertion respect to M-types before (P=0.002) and after 30 min (P=0.042) the morning session of HIIE. No significant changes during the evening training session were found. In conclusion, chronotype seems to significantly influence fatigue values, perceived exertions and vigour in relation to HIIE performed at different times of the day. Specifically, E-types will meet more of a burden when undertaking a physical task early in the day. Practical results suggest that performing an high intensity interval exercise at those times of day that do not correspond to subjects’ circadian preference can lead to increased mood disturbances and perceived exertion. Therefore, an athlete’s chronotype should be taken into account when scheduling HIIE.